2021
DOI: 10.1021/acs.chemmater.1c02159
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time X-ray Scattering Discovers Rich Phase Behavior in PbS Nanocrystal Superlattices during In Situ Assembly

Abstract: During the self-organization of colloidal semiconductor nanoparticles by solvent evaporation, nanoparticle interactions are substantially determined by the organic ligands covering the inorganic core. However, the influence of the ligand grafting density on the assembly pathway is often not considered in experiments. Here, we carry out an in situ synchrotron small-angle X-ray scattering and X-ray cross-correlation analysis study of the real-time assembly of oleic acid-capped PbS nanocrystals at a low ligand co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…These SL structural trends are congruent with previous studies on SL growth dynamics during evaporative self-assembly using other nanocrystal cores. , Many factors are known to influence nanocrystal assembly dynamics in solution, including size, shape and faceting, ligand density, concentration, and solubility. Among these factors, the starting nanocrystal size likely plays an important role in our CsPbBr 3 SL assemblies because the other factors remain constant in a single growth experiment. Several studies utilizing in situ X-ray scattering and theoretical modeling have elucidated how nanocrystal size impacts attractive (van der Waal’s) and repulsive (ligand sterics and osmotic pressure) interactions between individual nanocrystals in SL growth. These studies show that larger nanocrystals begin to assemble into ordered SLs at earlier time points and lower solution concentration than smaller nanocrystals due to their stronger attractive interactions.…”
Section: Sl Structural Trendssupporting
confidence: 87%
See 2 more Smart Citations
“…These SL structural trends are congruent with previous studies on SL growth dynamics during evaporative self-assembly using other nanocrystal cores. , Many factors are known to influence nanocrystal assembly dynamics in solution, including size, shape and faceting, ligand density, concentration, and solubility. Among these factors, the starting nanocrystal size likely plays an important role in our CsPbBr 3 SL assemblies because the other factors remain constant in a single growth experiment. Several studies utilizing in situ X-ray scattering and theoretical modeling have elucidated how nanocrystal size impacts attractive (van der Waal’s) and repulsive (ligand sterics and osmotic pressure) interactions between individual nanocrystals in SL growth. These studies show that larger nanocrystals begin to assemble into ordered SLs at earlier time points and lower solution concentration than smaller nanocrystals due to their stronger attractive interactions.…”
Section: Sl Structural Trendssupporting
confidence: 87%
“…Stronger associative interactions between larger QDs in the growth solution may cause these SLs to assemble into more strongly coupled local domains even when significant global disorder remains. 34 In summary, we have shown that STEM imaging coupled to FFT analysis is a facile method to characterize the structural properties of individual 3D SLs comprising cubic CsPbBr 3 QDs. The radial and angular FFT profiles provide information on the average QD CtC distance and size dispersity in the SL as well as the number of crystalline domains.…”
Section: Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…In situ SAXS, WAXS, GISAXS, and GIWAXS provide the possibility of studying the self-assembly kinetics and of understanding intermediate steps of superlattice formation. [26,73,74] For this a drop of colloidal nanocrystal dispersion is exposed to X-ray radiation and during the process of solvent evaporation scattered X-rays are probed in different angles depending upon the method. Once solvent evaporation starts, nanocrystals compress into ordered structures and X-ray scattering techniques with subsecond temporal and micrometer spatial resolution help to probe the stages of superlattice formation.…”
Section: In Situ Characterization: Tracking the Assembly In Real-timementioning
confidence: 99%
“…[24][25][26] Exposure of superlattices of oleic acid (OA) coated, cuboctahedral PbS and PbSe NPs to a nonpolar solvent (e.g., octane) was found to induce structural transformation between face-centered cubic (fcc), bodycentered-tetragonal (bct), body-centered cubic (bcc) or hexagonal closed-packed (hcp) structures. [11,24,27,28] Uptake of toluene was found to increase the interparticle distance and periodicity in superlattices of tetraoctylammonium bromide coated Au NP while exposure to ethanol resulted in an amorphous transformation. [20] However, while SAXS and WAXS can yield structural information of the superlattice, the observed superlattice structures and phase transitions have to the best of our knowledge not been related to quantitative information of the solvent amount and composition.In this study, time-resolved SAXS was used to study the structural transformation and lattice expansions during solvent removal of OA-coated iron oxide nanocube superlattices dispersed in a mixture of good and poor solvent with and without added OA.…”
mentioning
confidence: 99%